THE ROLE OF LAND TRANSPORTATION IN SUPPORTING THE NATIONAL TOURISM STRATEGIC AREA OF LAKE TOBA - Surya Immanuel Sihombing; Abdul Rahim Matondang; Satia Negara Lubis (Bajang Institute, 2022)
Lake Toba is a large natural lake in Indonesia located in the caldera of Mount Supervolcano. The Ajibata – Ambarita Crossing Route is one of 1 (one) of 6 (six) Crossings in the Lake Toba National Tourism Strategic Area. The 6 (six) crossing routes to Samosir Island currently in the Lake Toba National Tourism Strategic Area are the Ajibata – Ambarita Trail; Tigaras Trail – Samosir; Balige Trail – Onan Runggu; Muara – Sipinggan track; Muara Track – Onan Runggu; and the Ajibata – Tomok route. The aims of this research are: To analyze the level of fulfillment of service aspects in its implementation; and Improve wider outcomes and impacts on the development of land transportation in the Lake Toba National Tourism Strategic Area on the Ajibata - Ambarita Crossing. The research method used is descriptive research with a qualitative approach. The results of this study are based on SWOT analysis, the value is in a DEFENSIVE condition, namely the Threats value and Weakness value. The location of the port coordinates is in quadrant IV (Negative, Negative) which means that the port has weaknesses and threats from the internal aspects of the port.